Substitution behaviors among people who gamble during COVID-19 precipitated casino closures. Issue 3 (2nd September 2021) - Xuereb, Silas; Kim, Hyoun S.; Clark, Luke; Wohl, Michael J. A.
ABSTRACT: The COVID-19 pandemic triggered the closure of licensed casinos throughout the United States of America in March and April 2020. This study sought to examine how Americans who gamble responded to the COVID-19 lockdown, including migration to online gambling, and changes in substance use and use of other technologies. On 9 April 2020, we recruited an online sample of 424 Americans who gambled in the last three months via Amazon's Mechanical Turk. Self-reported changes in online gambling and other addictive behaviors since the onset of COVID-19 and problem gambling severity were measured. Overall, online gambling decreased following the onset of COVID-19 casino closures, while alcohol, tobacco, and cannabis use increased. Among respondents who reported no online gambling involvement prior to COVID-19, 15% reported migrating to online gambling. These migrators had higher levels of problem gambling and lower income than respondents who had never gambled online. The response to COVID-19 is heterogeneous: the majority of people who gamble reported reducing their online gambling but increased their substance use. A minority of people who gamble substituted casino gambling with online gambling. Because these individuals are characterized by problem gambling symptoms and lower income, they may be considered a vulnerable group.